Phenotypic Plasticity and Other Forage Responses to Grazing Management of Ecoturf Rhizoma Peanut. Issue 5 (10th August 2018) - Shepard, Erin M.; Sollenberger, Lynn E.; Kohmann, Marta M.; da Silva, Liliane Severino; Dubeux, Jose C.B.; Vendramini, João M.B.
Abstract : Forage–livestock systems in the southeastern United States are based on N‐fertilized perennial grass pastures, with minimal legume contribution. The legume rhizoma peanut (RP, Arachis glabrata Benth.) can persist and spread in grazed mixtures with C4 grasses, and Ecoturf RP is of particular interest because it is relatively decumbent and may vary its growth habit in response to defoliation management. The objective was to quantify effects of grazing frequency and intensity of Ecoturf on herbage accumulation (HA), canopy characteristics, storage organ mass, and total nonstructural carbohydrate (TNC) concentration. Treatments were the factorial combinations of three levels of regrowth interval (RI; 1, 4, and 7 wk) between grazing events and two levels of post‐grazing stubble height (SH; 4 and 8 cm). For the 4‐cm SH, HA increased from 8.4 to 10.5 Mg ha −1 in 2015 and from 9.8 to 13.6 Mg ha −1 in 2016 as RI decreased from 7 to 1 wk. The effect of RI was less pronounced for the 8‐cm SH. When grazed to a 4‐cm SH, herbage bulk density and post‐grazing leaflet mass increased linearly as RI decreased from 7 to 1 wk in both years. Changes in root‐rhizome mass and TNC pool during 2 yr of grazing were not affected by SH or RI. Ecoturf adapted to frequent, close grazing by increasing herbage bulk density and positioning leaves close to the soil surface, allowing rapid regrowth after defoliation without depleting reserves. Ecoturf is tolerant of a range of grazing strategies, showing promise for use in pastures.